Knowledge, attitudes, and practices of Lebanese women toward the use of oral contraceptive pills - Hajar Samaha; Linda Abou-Abbas; Zainab Barakat; Nathalie Lahoud (BMC Women's Health)
Abstract Background Despite widespread use, many Lebanese women have limited understanding of oral contraceptive pills (OCP), with misinformation and cultural barriers contributing to misuse and discontinuation. Additionally, the non-contraceptive benefits of OCP are often overlooked. Addressing these gaps can promote safer use and improve women’s health. This study aims to explore Lebanese women’s knowledge, attitudes, and practices regarding OCP and identify associated factors. Methods A cross-sectional study was conducted using a structured questionnaire among Lebanese women aged between 18- and 49-years old shopping in local pharmacies. Multivariable analyses were employed to investigate the factors associated with knowledge, attitude, practices toward OCP usage. Results A total of 384 women participated in the study, with 36.9% reporting ever using OCP. The mean knowledge score was 4.8 (SD = 1.5) out of 13, revealing notable knowledge gaps regarding OCP. Profession (medical employment), age, monthly family income, and OCP usage were all associated with knowledge, with profession showing the strongest association (β = 0.329, p < 0.001). Meanwhile, the mean attitude score was 3.8 (SD = 0.5) out of 6, suggesting an overall positive attitude towards OCP. Educational level (college/university vs. secondary or vocational or below, unstandardized β of 0.11, standardized β of 0.119, 95% CI of 0.01–0.21, P-value = 0.032) was associated with attitude. Additionally, age (AOR 1.05, 95% CI: 1.02–1.09), knowledge (AOR 1.20, 95% CI: 1.07–1.33), and monthly family income (>$2000 vs. $1,000, AOR = 0.46, 95% CI 0.24–0.91) emerged as significant factors associated with OCP usage. Conclusion The study revealed gaps in Lebanese women’s knowledge, attitude, and practices toward OCP, underscoring the need for accurate, patient-centered information. Providing this information in the context of decision-making empowers women to make informed contraceptive choices that align with their health needs and personal preferences.